Conceptualization of Believer's Character with Emphasis on the Concept of "Light" in the Holy Quran - Seyyede Sedighe Mirdadashi Kari; Hamid Rafiihonar (اخلاق وحیانی)
The concept of "light" in Quranic usages has comprehensive and fundamental meanings and has been used more than 43 times in various contexts. This research seeks the manifestation and embodiment of light in human beings as an aspect of the believer's character. The aim of the present study was to develop a conceptual model of the believer's character with emphasis on the concept of "light" in the Holy Quran. The qualitative content analysis method of Hsieh and Shannon (2005) was used in the form of conventional content analysis. For this purpose, three stages of coding were performed, and using 31 codes in the open coding stage, 83 axial codes in the first stage, and 22 axial codes in the second stage, a conceptual model of the believer's character with emphasis on the concept of "light" in the Quran was drawn. The research findings showed that five factors – rationality, belief in the unseen, connection with the Quran, internal locus of control, and belief in God's will – shape the believer's character; five factors – being requestable, being visible, being constructed in the world, being continuous, and being acquired – are the presuppositions of the believer's character; and twelve components – faith, being a follower of the Quran, internal stability, internal motivation, spiritual experiences, mental health, psychological well-being, striving for transcendence, life-giving happiness, purpose in life, self-actualization, and gratitude – are signs of the believer's character with emphasis on the concept of light in the Quran. In this regard, the believer's character can be introduced as a character that is connected to divine light and guidance, and therefore transmits light and guidance to others.